Optimization of Coconut Fibers Toward Heat Insulator Applications - YAAKOB, MOHD YUHAZRI; IP, HAERYIP SIHOMBING; A.R, JEEFFERIE; A.Z, AHMAD MUJAHID; A.G, BALAMURUGAN; M.N, NORAZMAN; A., SHOHAIMI (GLOBAL ENGINEERS & TECHNOLOGISTS REVIEW, 2011)
In this research, usage of coconut fibers and natural rubber as main materials for heat insulation application has been investigated. Both materials have significant advantages due to their high quality characteristic and abundant availability in Malaysia. Cold press technique was used to produce 12 different compositions of latex, which are 5 wt.%, 10 wt.%, 15 wt.%, 20 wt.%, 25 wt.%, 30 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, 55 wt.% and 60 wt.%. The result showed that composite specimen with 30 wt. % latex is the best compositions as it can absorb 95% of heat in the heat test. This is better than actual product that was made by synthetic rubber material. Also, the best result of the tensile test and compression test for the Young’s Modulus values are 33.473 kPa and 79.59 kPa respectively. Hence, the composite with 30 wt. % of natural latex is most suitable for the heat insulator application.